Proteomics Analysis of Candida albicans dnm1 Haploid Mutant Unraveled the Association between Mitochondrial Fission and Antifungal Susceptibility. Issue 1 (18th December 2019) - Truong, Thuyen; Zeng, Guisheng; Lim, Teck Kwang; Cao, Tong; Pang, Li Mei; Lee, Yew Mun; Lin, Qingsong; Wang, Yue; Seneviratne, Chaminda Jayampath
Abstract: Candida albicans is a major fungal pathogen, accounting for approximately 15% of healthcare infections with associated mortality as high as 40% in the case of systemic candidiasis. Antifungal agents for C. albicans infections are limited, and rising resistance is an inevitable problem. Therefore, understanding the mechanism behind antifungal responses is among the top research focuses in combating Candida infections. Herein, the recently developed C. albicans haploid model is employed to examine the association between mitochondrial fission, regulated by Dnm1, and the pathogen's response to antifungals. Proteomic analysis of dnm1Δ and its wild‐type haploid parent, GZY803, reveal changes in proteins associated with mitochondrial structures and functions, cell wall, and plasma membrane. Antifungal susceptibility testing revealed that dnm1Δ is more susceptible to SM21, a novel antifungal, than GZY803. Analyses of reactive oxygen species release, antioxidant response, lipid peroxidation, and membrane damages uncover an association between dnm1Δ and the susceptibility to SM21. Dynasore‐induced mitochondrial inhibition in SC5314 diploids corroborate the findings. Interestingly, Dynasore‐primed SC5314 cultures exhibit increased susceptibility to all antifungals tested. These data suggest an important contribution of mitochondrial fission in antifungal susceptibility of C. albicans . Hence, mitochondrial fission can be a potential target for combined therapy in anti‐ C. albicans treatment.